Secondary Metabolite from Phomopsis sp. Isolated from Plumeria acutifolia Poiret - and J. Muthumary, K. Nithya* (Recent Research in Science and Technology, 2010)
Abstract Plumeria acutifolia Poiret (Apocynaceae) contains eight species of mainly deciduous shrubs and tree, originated from Central America. Some species of this plant are used for the cure of rheumatism, diarrhoea, blennorhea, venereal disease and leprosy. Endophytes are the chemical synthesizers inside plants (Owen et al., 2004). Leaves of Plumeria acutifolia were submitted to isolation of endophytic fungi. The strain Phomopsis sp was selected for chemical and biological investigation because of the strong antibacterial activity and also rich source of secondary metabolites. Ethylacetate fraction of the fungus found to have terpenoid compound, which was further subjected to Thin layer chromatography (TLC), UV, FT-IR spectroscopic analysis. The terpenoid compound was found to have antibacterial activity whereas the same compound does not show any positive results towards human pathogenic Candida albicans. This is the first report of the isolation, cultivation of fungus Phomopsis sp and evaluation of antibacterial activity. Keywords: Apocynaceae, Antibacterial activity, Terpenoids, Endophytes, Phomopsis, Coelomycetes <span style="line-height: 200%; font-family: ";Arial Narrow";,";sans-serif";; letter-spacing: -0.3pt; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-SG; mso-bidi-language: AR-SA;" lang="EN-SG">